2015
DOI: 10.3892/etm.2015.2484
|View full text |Cite
|
Sign up to set email alerts
|

Reducing iron accumulation: A potential approach for the prevention and treatment of postmenopausal osteoporosis

Abstract: Postmenopausal osteoporosis (PMOP) is a systemic bone metabolism disease, characterized by progressive bone loss following menopause and a subsequent increase in fracture risk. Estrogen deficiency as a result of menopause is known to increase bone resorption and accelerate bone loss. Furthermore, postmenopausal women may exhibit iron accumulation, in addition to estrogen deficiency. Elevated iron levels are a risk factor for PMOP in postmenopausal women, and reducing the iron overload has been demonstrated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 57 publications
0
33
1
Order By: Relevance
“…Quantitative analysis of the area of mineralized bones (AMB) and cumulative optical density (COD) was performed as our previously described [ 27 , 28 ]. Images of the ventral aspect of larvae skulls (ARS stained) were acquired using the Inverted fluorescence microscope (Olympus IX71/IX81, Olympus Corporation, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative analysis of the area of mineralized bones (AMB) and cumulative optical density (COD) was performed as our previously described [ 27 , 28 ]. Images of the ventral aspect of larvae skulls (ARS stained) were acquired using the Inverted fluorescence microscope (Olympus IX71/IX81, Olympus Corporation, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The proline is an important osmotic adjustment substance. Previous studies have shown that proline can maintain the intracellular osmotic balance, thereby reducing the severity of cell damage when plants exposed to osmotic stress [18,19]. Three genes expressed in the two modules contained DUF221 domain, which were characteristic of calcium-permeable stress-gated channel proteins (Table S1).…”
Section: Transcriptome Co-expression Network Module Construction and mentioning
confidence: 99%
“…A significant percentage of HH patients develop low bone mass (74–79%), eventually resulting in OP (25–34%) that worsens with age [ 9 , 10 ]. HH-related OP results from the imbalance between bone formation and resorption leading to deterioration of bone microarchitecture and increased fracture risk [ 2 , 9 , 11 ]. OP onset and progression are subject to synergistic factors, such as a decrease in levels of estrogen and progesterone in postmenopausal women, associated with iron overload and oxidative stress [ 2 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…HH-related OP results from the imbalance between bone formation and resorption leading to deterioration of bone microarchitecture and increased fracture risk [ 2 , 9 , 11 ]. OP onset and progression are subject to synergistic factors, such as a decrease in levels of estrogen and progesterone in postmenopausal women, associated with iron overload and oxidative stress [ 2 , 11 ]. Nutrition is also an important variable in OP pathophysiology since a disruption of the nutritional equilibrium of several essential minerals, like Cu, Fe, Mg and Zn, as well as iron overload associated with diet and age, have been described as factors that can contribute to OP [ 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%